Speaking Out
XVIII, 264 p.
Keywords: Focusing on the female voice in public contexts, language and gender specialists consider the barriers and opportunities encountered by women in gaining recognition in politics, law, the church, education, business and the media, where people are increasingly judged by their speech and where male and female speech is often evaluated differently.